Performance and microstructure of MgO-SiO2 concrete under different environments - Sonat, Cem (2020)
This study investigated the changes in the performance and microstructure of MgO-SiO2 concrete under exposure to different environments involving carbonation, NaCl, MgCl2 and MgSO4 solutions for up to 180 days. Compressive strength results were compared to Portland cement (PC)-based concrete samples subjected to the same environments. Microstructural analysis performed via FESEM, XRD and TG/DTG indicated a lack of change in the composition of MgO-SiO2 samples. The sustained mechanical performance and the clear presence of hydrate phases such as brucite and M-S-H even after longer exposures highlighted the resistance of MgO-SiO2 formulations and their potential to be utilized in structural applications.